The Role of Social Services for Women Empowerment, Child Protection, Population Control and Family Planning in The Protection of Child Victims of Sexual Abuse - Nooriane, Joanita; Suratman, Teguh; Nurita, Riski Febria (Universitas Kristen Cipta Wacana, 2024)
This study aims to investigate the prevalence and nature of sexual abuse against children in the city of Malang, Indonesia, and to explore legal and social frameworks for the protection and Prevention of such abuse. The problem of the study is the increasing cases of child sexual abuse in Malang, despite legal and institutional efforts to protect them. The study used qualitative research design, involved interviews with key informants from the field of Child Protection of Social Services and analysis of relevant legal documents and regulations. The study found that sexual abuse of children in Malang includes various forms of non-physical and physical behavior, such as inappropriate comments, gestures, and unwanted physical contact. The implications of this study highlight the urgent need for further strengthening of legal protection, institutional capacity, and public awareness to effectively prevent and address the problem of child abuse in Malang.